STUDY ON THE INFLUENCE OF HEAT SINK STRUCTURE PARAMETERS ON MICRO-ENGINE CYLINDER CLOCK TEMPERATURE FIELD - LI KunQuan; WEN Rui (Jixie qiangdu)
Micro-engine was widely used in agricultural machinery and motorcycle equipment,especially in mower chain saws and other products by its advantages of simple structure,reliable operation and high efficiency. In this paper,ones built the3 D model for micro engines which was actually used,in addition,the steady temperature field of engine cylinder under rated speed was calculated by finite element analysis method of steady temperature field,finally,the key spots with high temperature distribution in engine cylinder radiator was obtained. A simplified model about the key parts of heat sinks is established to simulate the temperature influence law. Then,the influence of some main parameters like the spacing,number and thickness of the fins is studied. It is of theoretical significance to optimize the design parameters of micro-engine block structure and improve the heat dissipation of micro engine block.